Investigating the Response Amplitude Operator of a Heaving Pontoon under the Influence of a Submerged Trapezoidal Breakwater - Parviz Ghadimi; Mehdi Pourmostafa; Saeed Najafi (Advances in Civil Engineering)
Although breakwaters are of great importance to damp the wave energy and protect floating vessels/facilities, they are not fully successful in reducing the waves’ height. Therefore, special attention should be paid to accurately investigate the performance of breakwaters. In this paper, the efficiency of a submerged trapezoidal breakwater in the vicinity of a floating pontoon is numerically investigated. First, different simulations are conducted to calibrate the numerical model to achieve an optimum mesh size. Next, a test case is presented for simulation of regular waves passing over a submerged breakwater. Subsequently, the heave response amplitude operator (RAO) of a rectangular pontoon facing an incoming regular wave is studied. A comparison of the obtained results in both test cases with experimental data shows good compliance. Ultimately, the heave motion of a rectangular pontoon behind four different submerged trapezoidal breakwaters facing a regular wave is investigated and different parametric studies are conducted to assess the geometrical effect of the breakwaters. This is the main novelty of the present work which studies the effect of a breakwater on the response amplitude operator (RAO) of a floating structure. In fact, a new version of RAO is presented which includes both incident and transferred wave (which pass over the breakwater) affecting the floating body. Based on the acquired results, the modified RAO of the heaving pontoon shows that breakwater has no effect on the responding frequency, but it does reduce the amplitude of the exciting wave up to 30%.